Strategi Pemberdayaan Lahan Pekarangan di Kelurahan Banjarejo Kota Madiun - Luluk Sulistiyo Budi; Praptiningsih Gamawati Adinurani (Universitas Merdeka Madiun, 2021)
There are several factors that make yard empowerment less attractive to the community, so it is necessary to explore these problems from several aspects. Methods of implementing community service include (a) socialization of yardland empowerment that supports the RPL program and knowing the level of perception of prospective trainees, (b) plant cultivation training, (c) plant cultivation demonstration plots in the yard, and (d) assistance in managing yardland in a manner sustainable. The results of community service activities showed that after participating in the training there was (a) an increase in farming knowledge. (b) increasing the use of yardland by planting food crops, vegetable plants, ornamental plants or medicinal plants in accordance with land ownership (c) periodic assistance to support the sustainability of the yardland empowerment program.